2000
DOI: 10.1210/jc.85.8.2779
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pituitary Hormone Deficiency Caused by a Novel Mutation of a Highly Conserved Residue (F88S) in the Homeodomain of PROP-1

Abstract: Mutations in the pituitary-specific paired-like homeodomain transcription factor, PROP-1, result in combined pituitary hormone deficiency. We studied a Brazilian girl, offspring of first cousins, who presented with short stature and deficiencies of GH, TSH, PRL, LH, and FSH. Her cortisol response to hypoglycemia was determined at age 4.9, 10.7, and 14.1 yr and remained normal. Magnetic resonance imaging at the age of 9 yr revealed an anterior pituitary lobe of diminished height (3 mm; normal, 4.5 +/- 0.6), but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 0 publications
2
34
0
3
Order By: Relevance
“…It was thought that patients with a GHRHR molecular defect invariably have anterior pituitary hypoplasia (15,(25)(26)(27)(28)(29), and that GHRHR mutations can be excluded in the absence of this feature because GHRHR is critical for pituitary development and function of somatotroph cells (30)(31). However, patients homozygous for a GHRHR splice site mutation (IVS1 + 1G > A), presumably with molecular consequences identical to those documented in our patients, and with normal anterior pituitary have been reported recently (29).…”
Section: Description Of a New Ghrhr Mutation In Two Moroccan Patientssupporting
confidence: 62%
“…It was thought that patients with a GHRHR molecular defect invariably have anterior pituitary hypoplasia (15,(25)(26)(27)(28)(29), and that GHRHR mutations can be excluded in the absence of this feature because GHRHR is critical for pituitary development and function of somatotroph cells (30)(31). However, patients homozygous for a GHRHR splice site mutation (IVS1 + 1G > A), presumably with molecular consequences identical to those documented in our patients, and with normal anterior pituitary have been reported recently (29).…”
Section: Description Of a New Ghrhr Mutation In Two Moroccan Patientssupporting
confidence: 62%
“…The majority of these mutations are predicted to result in complete loss of function of the protein by ablating DNA binding and transcriptional activation. However, in vitro analysis has shown that some missense mutations retain partial activity (76,81,82). By far, the most common mutation (50-72% of all familial PROP1 mutations) (77,78,83), detected in multiple unrelated families from several different countries, is a 2 bp deletion among three tandem GA repeats ( 296 -GAGAGAG-302 ) within exon 2 resulting in a frameshift at codon 101 and the introduction of a termination codon at position 109 (often referred to as S109X), and probably represents a mutational hot spot within the gene, rather than a single common founder mutation (84).…”
Section: Prop1mentioning
confidence: 99%
“…F88, which corresponds to position 20 of the homeodomain in transcription factors of this class, constitutes the hydrophobic core of the first α-helix forming the homeodomain. This finding underscores the critical role of this highly conserved hydrophobic phenylalanine in the structure and function of the homeodomain of PROP-1 (19).…”
Section: Discussionmentioning
confidence: 55%
“…Brickman and cols. (19), analyzing 461 patients, found 5 patients of Afro-Caribbean descent with variable severity of SOD with this allelic variant (9). Analyzing the DNA of 42 normal individuals of Afro-Caribbean background, they encountered 5 individuals homozygous for the wild-type allele, 17 individuals homozygous and 20 heterozygous for the 59 A > G; N125S allelic variant.…”
Section: Discussionmentioning
confidence: 99%